Discovery of a novel highly specific, fully human PSCA antibody and its application as an antibody-drug conjugate in prostate cancer - Xiaojie Chu; Seungmin Shin; Du-San Baek; Liyong Zhang; Alex Conard; Megan Shi; Ye-Jin Kim; Cynthia Adams; Maggie Hines; Xianglei Liu; Chuan Chen; Zehua Sun; et al. (mAbs)
Prostate stem cell antigen (PSCA) is expressed in all stages of prostate cancer, including in advanced androgen-independent tumors and bone metastasis. PSCA may associate with prostate carcinogenesis and lineage plasticity in prostate cancer. PSCA is also a promising theranostic marker for a variety of other solid tumors, including pancreatic adenocarcinoma and renal cell carcinoma. Here, we identified a novel fully human PSCA antibody using phage display methodology. The structure-based affinity maturation yielded a high-affinity binder, F12, which is highly specific and does not bind to 6,000 human membrane proteins based on a membrane proteome array assay. F12 targets PSCA amino acids 63–69 as tested by the peptide scanning microarray, and it cross-reacts with the murine PSCA. IgG1 F12 efficiently internalizes into PSCA-expressing tumor cells. The antimitotic reagent monomethyl auristatin E (MMAE)-conjugated IgG1 F12 (ADC, F12-MMAE) exhibits dose-dependent efficacy and specificity in a human prostate cancer PC-3-PSCA xenograft NSG mouse model. This is a first reported ADC based on a fully human PSCA antibody and MMAE that is characterized in a xenograft murine model, which warrants further optimizations and investigations in additional preclinical tumor models, including prostate and other solid tumors.